The Level of Hardiness of Individuals with Different Strategies of Self-Affirmation as a Factor of Psychologically Safe Educational Environment - Babiy A. I. (Psychologically Safe Educational Environment: Design Problems and Development Prospects, 2020)
to create a psychologically safe educational process, the most important components will be the personal characteristics of the participants in the educational process. The purpose of this study was to determine the level of hardiness of future specialists with different strategies of self-affirmation as a fac-tor affecting the psychological safety in the educational environment. It is vitality that is one of the basic characteristics that allows participants in the educational process not only to overcome life circumstances and adapt to constantly changing conditions, but also to become stronger, qualitatively improving the standard of living, physical and psychological health. An analysis of the empirical data obtained was presented, as well as the features of psychological and pedagogical support aimed at increasing the resilience of individuals with different self-affirmation strategies.
Keywords: психолого-педагогическое сопровождение; образовательная среда; educational environment; жизнестойкость; psychological and pedagogical support; стратегия самоутверждения; hardiness; strategy of self-affirmation